2014
DOI: 10.17522/nefefmed.71261
|View full text |Cite
|
Sign up to set email alerts
|

GeoGebra Kullanımının Önlisans Matematik Öğretimine Etkinliğinin İncelenmesi

Abstract: -The purpose of this study is to investigate the effects of GeoGebra software assisted instruction on vocational school students' academic achievement and their attitudes towards mathematics. Furthermore,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
2
2
0
4
Order By: Relevance
“…Findings of the quantitative analysis revealed that there was no statistically significant difference between the experimental and control groups in terms of achievement level. This result consistent with the result of Demirbilek and Özkale's (2014) study. Demirbilek and Özkale (2014) found that DG based instructions does not increase students' mathematics achievement.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Findings of the quantitative analysis revealed that there was no statistically significant difference between the experimental and control groups in terms of achievement level. This result consistent with the result of Demirbilek and Özkale's (2014) study. Demirbilek and Özkale (2014) found that DG based instructions does not increase students' mathematics achievement.…”
Section: Discussionsupporting
confidence: 93%
“…This result consistent with the result of Demirbilek and Özkale's (2014) study. Demirbilek and Özkale (2014) found that DG based instructions does not increase students' mathematics achievement.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Using computers as supporting materials on education by increasing opportunities for technology could be made abstract theories more understandable. The researchers have discovered that the results of success are quite effective in using dynamic geometry software [1][2][3][4][5][6][7][8]. Therefore, some lectures are with computer applications supported, which continuously user-friendly developed and designed.…”
Section: Introductionmentioning
confidence: 99%
“…Karadağ ve McDougall (2009) teknolojiyle oluşturulan görsel ve hareketli öğrenme ortamlarının, sadece matematiksel kavramların öğretimi sırasındaki kullanılan öğretim ve öğrenme stratejileri açısından değil aynı zamanda matematik eğitiminin içeriği açısından da katkıları olabileceğini belirtmektedirler. Yapılan bir çok araştırmada teknolojinin matematik eğitiminde kullanılmasının öğrencilerin başarılarını arttırdığı görülmüştür (Baydaş, Göktaş ve Tatar, 2013;Demirbilek ve Özkale, 2014;Dikovic, 2009;Doğan ve İçel, 2011;Selçik ve Bilgici, 2011;Şataf, 2009;Yavuzsoy-Köse ve Özdaş, 2009;Yazlık ve Ardahan, 2012;Yılmaz, Ertem ve Güven, 2010;Zengin, Furkan ve Kutluca, 2012).…”
Section: Introductionunclassified